(3ebGdI aj Gdcd hGdCLRGAs - (3CHh RcQjG jMji Hf YOj Hf RcQjG GdajdSha GdfUQGfj GdjYbhHjs
(3ChdgG (B:s
(3bGd Efi deG QCjJ ENJdGa GdfXGQjf ai CMhGd cd hGdGLRGA hJHGjf CQGFge ajgG aEf HYVge QCi Cf Gdcd Gdcd djS gh TjFkG ZjQ CLRGFg s
(3BNQgG (B:s
(3hef MjK gh EfSGf aEf PGJ GdGfSGf GdeQcHI fe gPG GdeGOI hef GdhUhQI aVd hTQa ef LejY GdeQcHGJ GdcGFfI GdaGSOI abO fHFfG Ydi YQVfG ai gPG GdebGdI hhajfG eG hYOfG Hg ai aGJMJgG HeYhfg Gddg hMSf Jhajbg hddg GdMeO OGFekG hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(2558) s
Keywords: (3GdadSaI hGdefWbs